2018
DOI: 10.1038/s41598-017-19004-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene and MicroRNA Perturbations of Cellular Response to Pemetrexed Implicate Biological Networks and Enable Imputation of Response in Lung Adenocarcinoma

Abstract: Pemetrexed is indicated for non-small cell lung carcinoma and mesothelioma, but often has limited efficacy due to drug resistance. To probe the molecular mechanisms underlying chemotherapeutic response, we performed mRNA and microRNA (miRNA) expression profiling of pemetrexed treated and untreated lymphoblastoid cell lines (LCLs) and applied a hierarchical Bayesian method. We identified genetic variation associated with gene expression in human lung tissue for the most significant differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…MicroRNAs (miRNA or miR) is a class of small, non-encoding RNA molecules (7). miRNAs serve important roles in several biological and pathological processes by promoting mRNA degradation or inhibiting mRNA translation, to negatively regulate target gene expression (8).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNA or miR) is a class of small, non-encoding RNA molecules (7). miRNAs serve important roles in several biological and pathological processes by promoting mRNA degradation or inhibiting mRNA translation, to negatively regulate target gene expression (8).…”
Section: Introductionmentioning
confidence: 99%
“…They control gene expression by combining with the messenger RNAs (mRNAs) of target genes, causing mRNA degradation or translation suppression (6,7). Numerous studies have demonstrated that the aberrant and disordered expression of miRNAs is involved in many malignant tumors, including LCs (812).…”
Section: Introductionmentioning
confidence: 99%
“…MTHFD2 is regulated directly by several miRNAs in different cancer cells. For example, hsa‐miR‐202 has been predicted to target MTHFD2 in lung cancer with MTHFD2 showing enhanced expression and hsa‐miR‐202 exhibiting lessened expression after pemetrexed exposure . In breast cancer miR‐9 more directly targets and inhibits MTHFD2 to suppress the proliferation of breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%